2010
DOI: 10.1182/blood-2009-12-259598
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 regulates graft-versus-host disease

Abstract: Suppressor of cytokine signaling-3 (SOCS3) is the main intracellular regulator of signaling by granulocyte colony-stimulating factor, an immune-modulatory cytokine used to mobilize stem cells for transplantation. We have therefore studied the contribution of SOCS3 to the spectrum of graft-versus-host disease (GVHD) after allogeneic stem cell transplantation (SCT). Grafts from SOCS3 ؊/⌬vav donor mice in which SOCS3 deficiency is restricted to the hematopoietic compartment had an augmented capacity to induce acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
1
35
1
Order By: Relevance
“…15,32,34 This dual expression has been attributed to epigenetic suppression of the regulatory protein SOCS3, 32 whose absence in donor T cells we have shown to also result in polyfunctional T-cell responses and exacerbated GVHD. 44 In this study, we found that Socs3 gene expression was downregulated in CD8 Table 3). These data suggest that differential expression of Socs3 may also drive the hyperproinflammatory T-cell phenotype observed in iTc17.…”
Section: Yfpmentioning
confidence: 53%
“…15,32,34 This dual expression has been attributed to epigenetic suppression of the regulatory protein SOCS3, 32 whose absence in donor T cells we have shown to also result in polyfunctional T-cell responses and exacerbated GVHD. 44 In this study, we found that Socs3 gene expression was downregulated in CD8 Table 3). These data suggest that differential expression of Socs3 may also drive the hyperproinflammatory T-cell phenotype observed in iTc17.…”
Section: Yfpmentioning
confidence: 53%
“…The molecular mechanism for this is unknown. Furthermore, genetic deletion of SOCS3, the endogenous negative regulator of STAT3, exacerbates graft versus host disease, a model of SSc (23).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of serum cytokines levels was performed using cytokine bead array as described previously (39). Staining for cell surface markers was also performed as described previously (40,41).…”
Section: Generation Of Smg1mentioning
confidence: 99%